COMPETENCIES POSSESSED BY UPPER BASIC EDUCATION LEVEL TEACHERS FOR TEACHING BUSINESS STUDIES FOR EFFECTIVE SERVICE DELIVERY IN ANAMBRA STATE (NAU Journal of Technology and Vocational Education, 2024)
The study was designed to find out the competencies possessed by upper basiceducation level teachers for teaching business studies in Anambra State. The studywas guided by three research questions and three null hypotheses. The study adoptedsurvey research design. Questionnaire was the instrument used for data collection.Mean and standard deviation were used to answer the research questions while t- testwas used for hypotheses testing. The result indicated that out of the twenty twocompetencies identified by the study, only eleven were possessed by the businessstudies teachers. The competencies possessed included among others; selecting thetopic to be taught, stating specific objectives to be achieved, effective knowledge ofthe subject matter as well as relating course of study to measurable performanceobjectives. However, the competencies not possessed by the teachers include amongothers; proper hanging of charts and pictures and constructing valid and reliable testto evaluate students’ progress. It was found out that there was no gender biasregarding the competencies possessed by teachers. The recommendations amongothers were that; all the identified competencies which the business studies teachersneeded to improve on be packaged for use during in- service training of teachers inAnambra State and that government should organize seminars and workshops forteachers in the areas of the identified competencies lacking for improvement.